2020
DOI: 10.3390/smartcities3040059
|View full text |Cite
|
Sign up to set email alerts
|

Use of Social Media to Seek and Provide Help in Hurricanes Florence and Michael

Abstract: During hazardous events, communities can use existing social media networks to share information in real time and initiate a local disaster response. This research conducted a web-based survey to explore two behaviors around the use of social media during hurricanes: seeking help and responding to help requests. Through the survey, we sampled 434 individuals across several counties affected by 2018 hurricanes Florence and Michael, which were both designated by the National Oceanic and Atmospheric Administratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…In the case of Weibo, users can connect these two groups of people by both retweeting and commenting on help-seeking messages ( Sharp & Carter, 2020 ). Besides, people who are exposed to a higher proportion of help-seeking messages in their information feed tend to provide physical help ( DiCarlo & Berglund, 2020 ), suggesting the importance of continuous and repeated diffusion of help-seeking messages. The more times one message is shared, the higher chance it might have to reach help-providers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the case of Weibo, users can connect these two groups of people by both retweeting and commenting on help-seeking messages ( Sharp & Carter, 2020 ). Besides, people who are exposed to a higher proportion of help-seeking messages in their information feed tend to provide physical help ( DiCarlo & Berglund, 2020 ), suggesting the importance of continuous and repeated diffusion of help-seeking messages. The more times one message is shared, the higher chance it might have to reach help-providers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Social networks have become an essential part of our daily lives, documenting people's movements, experiences, and emotions, including information about events in which they are involved. Research has shown that real-life events, including personal ones, leave their mark on social media [12,13]. It happens through the direct mentioning of the event or changes in patterns of users' behavior on social media.…”
Section: Related Workmentioning
confidence: 99%
“…Örneğin Florence ve Michael kasırgaları sırasında sosyal medya platformları yardım aramak veya yardım sağlamak amacıyla kullanılmışlardır. 4 Ayrıca benzer örnekler Haiti depremi ve Japonya tsunamisi gibi afetler sırasında da görülmüştür. Abbasi ve ark.…”
Section: Introductionunclassified